The use of sulfonamides in the Spanish Civil War: The publication of doctors D'Harcourt, Folch and Oriol in 1938 - Elola Ramón, Juan Julián (Hispania Nova, 2021)
During the Spanish Civil War, both armies tested new medical and surgical techniques. Among others, the use of antibacterial agents, which were still under development. This fact is little known, since the acquired experience was hardly ever transmitted. Only the study carried out at Vallcarca Hospital, in Barcelona, in the spring of 1938, by D'Harcourt, Folch and Oriol, published in the Revista de Sanidad de Guerra, was documented. The observations collected in his research allow to know the conditions of the tests and the impression that the results of the first simple medical treatment against infections caused. There is other evidence that the use of sulfonamides was more frequent and occurred in different parts of Spain, at least since the beginning of 1938. This article attempts to complete the scarcity of data on this aspect, compiling and analyzing the information found and reviewing that of D'Harcourt et al.
Keywords: Spanish Civil War; Sulfonamide; Amido-sulfol®; Prontosil®; Para-aminophenylsulfamide; Vallcarca Hospital